A review article on medicinal importance of Alysicarpus monilifer - Sharma , Manoj Kumar; Narayan, Govind; Chaturvedi, Shashikant (International Research Journal of Ayurveda & Yoga, 2024)
For achieving the superlative ends consisting of morality, prosperity, artistic values and sacred freedom, health is considered as a precondition. The main components of the model of positive healthiness are preventative and curative aspects of disease. Therapeutic plants engaged an important place in the socio-cultural, spiritual and medicinal field of rural people of India. One such medicinal plant is Alysicarpus monilifer also known as Krishna barani/ Chitrabarani, is a Fabaceae family. The various ailments of Alysicarpus monilifer is Analgesic effect, Hepatoprotective effect, Anti inflammatory effect. Research works are going on to discover the wide area of applications of Alysicarpus monilifer. This review article delineates the therapeutic effectiveness Alysicarpus monilifer.